Interpersonal relationships among nurses. Quality of care the adult patient. Edgardo Rebagliati Martins National Hospital - Cheppe-Vidal, Aida E. (2019)
The goal of the present research was to determine the interpersonal relationships in nurses and the quality of the attention given by the patient from the Emergency Service of adults at Edgardo Rebagliati Martins National Hospital during the month of April in 2012.The study was prospective, transversal and correlational study that evaluated 78 nurses through a survey to determine the level of their interpersonal relationships and 234 patients using a survey that determines the quality of nursing care received. The chi square test was applied in the statistical analysis of the two variables. The results obtained were that 55.1 % of the nurses considered that interpersonal relationships among colleagues were bad. The 57.7% of patients considered as regular the attention received by the nurse and 17.5% considers it good. It was found a Chi-square 12.11 with a p<0.05, with the conclusion that there is a degree of dependency between the level of interpersonal relationships among nurses and the quality of care provided to patients.